2018
DOI: 10.1016/j.ccell.2018.10.015
|View full text |Cite
|
Sign up to set email alerts
|

A Transcription Factor Addiction in Leukemia Imposed by the MLL Promoter Sequence

Abstract: Summary The Mixed Lineage Leukemia gene (MLL) is altered in leukemia by chromosomal translocations to produce oncoproteins comprised of the MLL N-terminus fused to the C-terminus of a partner protein. Here, we used domain-focused CRISPR screening to identify ZFP64 as an essential transcription factor in MLL-rearranged leukemia. We show that the critical function of ZFP64 in leukemia is to maintain MLL expression via binding to the MLL promoter, which is the most enriched location of ZFP64 occupancy in the huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 61 publications
5
58
0
Order By: Relevance
“…SEM cells infected with the pooled library of sgRNAs were collected at day 0 and day 12 to sequence for sgRNA distribution (Figure 6C). In accordance with prior genome-wide CRISPR screens and functional studies in B-ALL, many survival dependent genes were identified in the top 50 genes in our screen including PAX5 , DOT1L , ZFP64 , YY1 , MEF2C , MYC and KMT2A (26, 29, 50, 51). USF2 was ranked as the top 24 th essential gene in MLLr SEM cells (Figure 6D).…”
Section: Resultssupporting
confidence: 83%
“…SEM cells infected with the pooled library of sgRNAs were collected at day 0 and day 12 to sequence for sgRNA distribution (Figure 6C). In accordance with prior genome-wide CRISPR screens and functional studies in B-ALL, many survival dependent genes were identified in the top 50 genes in our screen including PAX5 , DOT1L , ZFP64 , YY1 , MEF2C , MYC and KMT2A (26, 29, 50, 51). USF2 was ranked as the top 24 th essential gene in MLLr SEM cells (Figure 6D).…”
Section: Resultssupporting
confidence: 83%
“…The first identified cancer‐associated TFs were fusion proteins in leukemia cells (Table 1). Accumulating lines of evidence have revealed that these fusion proteins function as drivers of disease onset and progression by inhibiting cell differentiation and maintaining a more stem cell‐like state 4,5 . Recently, cancer‐associated TFs that promote invasiveness and metastasis of solid tumors have also been identified (Table 1).…”
Section: Cancer‐associated Tfs Are a Promising Target For Cancer Therapymentioning
confidence: 99%
“…Another example of clustered homotypic TF binding sites associated with gene control is the binding of ZFP64 to the MLL gene promoter, activating the expression of the chromatin regulator MLL, although in this case ZFP64 shows a limited set of additional direct target genes 32 . CHD4 is an especially abundant nuclear protein in erythroid precursors 33 .…”
Section: Discussionmentioning
confidence: 99%